Balance of academic studies on cultural industries in the coffee region (1987-2007) (2019)
This paper provides a fi rst comparison aroundacademic studies on cultural industries in the Coffee Regioncarried out within the past two decades. The work, whichis close to the scope of a state of the art, determined by thethematic interests, methodological approaches, theoreticalperspectives and contexts of production present in 88 titlesfound in fi ve universities in the departments of Caldas,Quindío and Risaralda. It also ordered the informationcollected by subject and title indexes, which are useful forall the people who are interested in the subject.